Videoconference microscopy is a reliable alternative to conventional microscopy in the evaluation of Barrett's esophagus: Zooming into a new era. Issue 4 (23rd September 2021) - Axley, Page; Mitchell, Rachel; Council, Leona; Patel, Chirag; Tracht, Jessica; Collingwood, Robin; Harrison, Devin; Redden, David; Beasely, Mark; Kabir Baig, Kondal Kyanam R; Al Diffalha, Sameer; Peter, Shajan
Abstract: Telepathology, practicing pathology from a distance, allows experts to review cases without the need to transfer glass slides. Due to significant intra- and inter-observer variabilities in the histological evaluation of Barrett's esophagus (BE), current guidelines recommend expert consultation in cases of dysplasia. We aimed to determine whether telepathology using microscope videoconferencing can be reliably used for evaluation of BE. Biopsies from 62 patients with endoscopic findings of salmon colored mucosa extending ≥1 cm proximal to the gastroesophageal junction were randomly selected to represent benign esophagus, non-dysplastic BE, low-grade dysplasia, high-grade dysplasia, and adenocarcinoma. Three gastrointestinal-trained pathologists reviewed the cases via videoconference microscopy followed by conventional microscopy. Intra-observer and pairwise inter-observer agreements between the conventional microscopy and videoconference methodologies were calculated for each of the three pathologists using Fleiss-Cohen weighted kappa ( K ) analysis. The intra-observer agreement for each pathologist's assessment of videoconference microscopy and glass slide readings showed very good reliability ( K = 0.94, 95% confidence interval = 0.89–0.99; 0.88, 95% confidence interval = 0.79–0.98; 0.93, 95% confidence interval = 0.90–0.97). Mean pairwise inter-observer agreement was 0.90 for videoconference and 0.91 for conventional microscopy. Diagnosis and grading of BE using videoconference microscopy show similar reliability as conventional microscopy. Based on our findings, we propose that videoconferencing pathology is a valid instrument for evaluating BE.